Zastosowanie metody DEA w ocenie efektywności zarządzania portfelem funduszu - Zamojska-Adamczak, Anna (Efficiency of mutual fund and a data envelopment analysis, 2006)
The paper presents an application of the DEA method to measure the efficiency of equity mutual funds on the polish capital market. The DEA method is widely employed in operational research to compute the relative measure of efficiency and it can be applied also for the mutual fund performance. Results showed, that DEA is a new (alternative) measure of performance that seeks to address the limitation of the popular (traditional) indices of performance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 112-119